PENELUSURAN AKTIVITAS ANTIBIOFILM DAN FORMULASI SPONS Petrosia sp. SEBAGAI NANOGEL PENYEMBUH LUKA ULKUS DIABETIKUM AKIBAT INFEKSI BIOFILM Staphylococcus aureus - Arifin Nur Fahdianto; Nur Atika Astriani; Virgiawan Yoga Pratama; Hasyrul Hamzah; Indra Yudhawan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Diabetic ulcers are known to be one of the most feared complications and account for 80% of hospital admissions in patients with Diabetes Mellitus (DM). Diabetic ulcers occur due to bacterial infections, exacerbated by the formation of biofilm in the wounds. Nanotechnology presents a new alternative strategy for inhibiting biofilm formation, one of which is nanogel. The richness of marine biota that has the potential as an anti-biofilm candidate includes Petrosia sp. This study aims to extract and test the anti-biofilm activity of the Petrosia sp. formulation as a nanogel for healing diabetic ulcers caused by biofilm infection of Staphylococcus aureus. The extraction method used is maceration with 96% ethanol as a solvent, and biofilm activity is determined using the microtiter broth method. The procedure for creating incisional wounds on male mice induced with diabetes by alloxan is performed after shaving the fur in the area to be incised, followed by the application of 2% lidocaine cream as a local anesthetic. Subsequently, a preclinical trial on male mice is conducted by monitoring the stages of S. aureus biofilm wounds in both the test group and the positive control group. The results show that the nanogel formula from Petrosia sp. can inhibit up to 78.04% ± 0.01 on diabetic ulcer wounds with S. aureus biofilm over a period of 10 days and is highly potential to be developed as a new anti-biofilm candidate for diabetic ulcers caused by S. aureus biofilm.